The effectiveness of accelerated cultivation of degraded agrarian sod-podzolic soil in crop rotations of different intensity - A. I. Ivanov; Zh. A. Ivanova; P. A. Filippov (Аграрная наука Евро-Северо-Востока, 2024)
The hidden depleting degradation of the effective fertility of previously cultivated agrarian sod-podzolic soils is one of the most significant risks for the development of agriculture in the Non-Chernozem region and its food security. In a stationary long-term experiment, established in the Leningrad region in 2006, a comprehensive assessment of the effectiveness of accelerated cultivation of degraded sandy loam agrarian sod-podzolic soil to a good and high level of cultivation was performed. The objects of the research were three types of soil (medium-, well- and highly cultivated) and crops of cereal and row six-field crop rotations, cultivated in a three-variant scheme of a complete mineral fertilizer system. During the study in the second rotation of crop rotations (2012–2016), it has been established that the responsiveness of crops to accelerated soil cultivation and complete mineral fertilizer is determined by a combination of their biological and varietal characteristics with weather, climatic and phytosanitary conditions. The average annual productivity level of studied crop rotations on medium-cultivated soil amounted to 3.9 and 3.8 thousand grain units per ha. On well–cultivated and highly cultivated soil the productivity increased by 34 and 67, 50 and 86 %, respectively, and from the use of a complete mineral fertilizer system – by 28 and 18 %, respectively. The level of profitability of soil cultivation varied from 51–97 % in the crop rotation with cereals, and to 234–301 % in the row crop rotation with an average annual net yield of 12.1–13.1 and 97.1–110.4 thousand rubles/ha. The payback period for accelerated cultivation to a good and high level was 3.3 and 5.1 years in the crop rotation with cereals and 0.6 and 1.2 years in the row crop rotation, respectively.